The relationship between risk of bias criteria, research outcomes, and study sponsorship in a cohort of preclinical thiazolidinedione animal studies: a meta‐analysis - Abdel‐Sattar, M. (Evid Based Preclin Med, 2014)
INTRODUCTION: There is little evidence regarding the influence of conflicts of interest on preclinical research. This study examines whether industry sponsorship is associated with increased risks of bias and/or effect sizes of outcomes in published preclinical thiazolidinedione (TZD) studies. METHODS: We identified preclinical TZD studies published between January 1, 1965, and November 14, 2012. Coders independently extracted information on study design criteria aimed at reducing bias, results for all relevant outcomes, sponsorship source and investigator financial ties from the 112 studies meeting the inclusion criteria. The average standardized mean difference (SMD) across studies was calculated for plasma glucose (efficacy outcome) and weight gain (harm outcome). In subgroup analyses, TZD outcomes were assessed by sponsorship source and risk of bias criteria. RESULTS: Seven studies were funded by industry alone, 17 studies funded by both industry and non‐industry, 49 studies funded by non‐industry alone and 39 studies had no disclosures. None of the studies used sample size calculations, intention‐to‐treat analyses, blinding of investigators or concealment of allocation. Most studies reported favourable results (88 of 112) and conclusions (95 of 112) supporting TZD use. Efficacy estimates were significantly larger in six studies sponsored by industry alone (−3.41; 95% CI −5.21, −1.53; I(2) = 93%) versus 42 studies sponsored by non‐industry sources (−0.97; 95% CI −1.37, −0.56; I(2) = 81%; p‐value = 0.01). Harms estimates were significantly larger in four studies sponsored by industry alone (5.00; 95% CI 1.22, 8.77; I(2) = 93%) versus 38 studies sponsored by non‐industry sources (0.30; 95% CI −0.08, 0.68; I(2) = 79%; p‐value = 0.02). TZD efficacy and harms did not differ by disclosure of financial COIs or risks of bias. CONCLUSIONS: Industry‐sponsored TZD animal studies have exaggerated efficacy and harms outcomes compared with studies funded by non‐industry sources. There was poor reporting of COIs.